Absorptive capacity and innovation in low-tech companies in emerging economies - Del Carpio, Javier Fernando (2018)
Innovation capacity is on the focus of policy makers in emerging economies. Although some studies show the antecedents of innovation capacity for developed economies and high technological industries, scant research outcomes exist for different settings. This study tries to shed some light on the drivers of innovation capacity for low technological companies in emerging economies. Using the absorptive capacity as a driver of technological and non-technological innovation capacity, this study proposes a SEM model to contribute to the literature of innovation capacity including technological and non-technological innovation, and the relationship between them, in low-techonology industries in an emerging economy. A sample of 706 manufacturing companies from Peru is used. The academic contribution of this study states that absorptive capacity favors technological and non-technological innovation capacity and that non-technological innovation affects technological one. Accordingly, managerial contribution suggests improving absorptive capacity levels to internal R&D activities but also to organizational and marketing innovation activities.